A Broad-Spectrum Microbicide with Virucidal Activity against Sexually Transmitted Viruses - Howett, M. K. (American Society for Microbiology, 1999)
Sodium dodecyl sulfate (SDS), an alkyl sulfate surfactant derived from an organic alcohol, possesses surfactant properties but also denatures and unfolds both monomeric and subunit proteins. In preliminary experiments, we demonstrated that SDS is a potent inactivator of herpes simplex virus type 2 and human immunodeficiency virus type 1 at concentrations comparable to those used for the surfactant nonoxynol-9. We hypothesized that SDS might be capable of denaturing the capsid proteins of nonenveloped viruses. In this report, we demonstrate inactivation of rabbit, bovine, and human papillomaviruses after brief treatment with dilute solutions of SDS. Effective concentrations were nontoxic to rabbit skin and to split-thickness grafts of human foreskin epithelium. This is the first report of a microbicidal surfactant that will inactivate papillomaviruses. We propose that SDS is now a candidate microbicide for formulation and testing with humans.